Improving English Vocabulary for Second Graders Using Pictures at SD Pangudi Luhur Jakarta - Handayani, Nur Fajar (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2018)
AbstractThe research was conducted to investigate the role of Pictures as the teaching media in improving the Second Graders’ English vocabulary at SD Pangudi Luhur, Jakarta in Academic Year 2016/2017. To achieve the objective, the data were collected through the tests, questionnaires and observer’s sheet. The respondents consisted of 25 students. The result showed that pictures as teaching media could improve the students’ vocabulary, proved by the increase of the mean score of the pre-test and post-test 1 and 2: 61.32; 70.48; and 81.08. The findings were also strengthened by the respondents’ positive attitudes towards the media used collected through questionnaires.Keywords: vocabulary, pictures, classroom action research